Analysis of factors affecting the Environmental Quality Index (EQI) and its implications for sustainable development - Kusumadewi, Dzikrina Almas; Kristanto, Bimo Yudo (Journal of Sustainability, Society, and Eco-Welfare, 2025)
Background: The Environmental Quality Index (EQI) reflects environmental performance and sustainability, with DKI Jakarta scoring 54.57—below its target. This study analyzes the influence of the Human Development Index (HDI), population growth, and the Information, Communication, and Technology Development Index (IDI) on DKI Jakarta’s EQI. Methods: A quantitative approach using time-series data (2008–2023) and multiple linear regression analysis was applied to evaluate the relationship between HDI, population growth, and IDI with environmental quality. Findings: HDI positively impacts environmental quality, contributing 5.776%. In contrast, a 1% increase in IDI and population growth correlates with a 2.183% and 173.456% decline in EQI, respectively, highlighting the environmental challenges of urbanization and technological expansion. Conclusion: Improving human resources, adopting green technologies, and fostering collaboration among stakeholders are critical to enhancing environmental quality. Novelty/Originality of this article: This study provides new insights into the interplay of HDI, IDI, and population growth in influencing environmental quality in a major urban area.